Desafios e perspectivas para o trabalho coletivo entre professores no âmbito do desenvolvimento da Proposta de Reestruturação Curricular do Ensino Médio no RS - Kerber, Fernanda (2015)
This research aims to understand how the operating conditions for carrying out actions related to collective work during interactions between SI teachers and teachers of other disciplines that make up the curriculum of secondary education in the context of the implementation process of the Restructuring Proposal Curriculum of Secondary Education (PREM) under the coordination of the Secretary of the State Education RS (SEDUC / RS). To achieve this goal, we propose to answer the following research question: To what extent teaching practices developed in the interactions between SI teachers and teachers of other disciplines that make up the curriculum of high school, have characteristics of collective work? We take as sources of information: (1) 09 Teachers responsible for SI; (2) 09 Teachers responsible for other disciplines that make up the current curricular matrices of high school and; (3) (09) members of Pedagogical Coordination of state schools of Eastern RS Education. Used as instruments to collect information on these subjects, basically individual interviews. From the data collected information we can say that there was no awareness that it should be made a collective work, which articulate teachers of different areas of knowledge, development of projects to be developed in the IS discipline. The planning of these activities was the responsibility almost entirely, SI teacher himself, with a little help from members of the Pedagogical Coordination of schools. There is no involvement of all teachers in the proposal, as teachers of other subjects, at no time sought the professor SI to develop some activity together. Hardly the collective teaching work will establish in schools without the Pedagogical Coordination guarantees periodically, discussion spaces and activity planning among teachers. We conclude that, without specific training for all school teachers, to carry out projects that combine different curriculum components for the planning, hardly there will be a collective teaching.